POGLĄDY POLSKICH NAUCZYCIELI NA UŻYCIE JĘZYKA PIERWSZEGO W ROZWIJANIU OBCOJĘZYCZNEJ KOMPETENCJI KOMUNIKACYJNEJ - Róg, Tomasz (Neofilolog, 2019)
Although a dominating paradigm in foreign language teaching in the past decades has been to use foreign language as often as possible, voices are now being raised that there is a place for students’ mother tongue in a language classroom. As the present article shows, both the critics and the supporters of the monolingual principle put forward commonsensical arguments in support of their stands. These arguments are outlined in the first part of the present article together with a brief look at the history of foreign-language-only approaches in language teaching methodology. What follows is a report on a study conducted by the author among 20 teachers in Poland with the aim of finding out the extent of and reasons for using mother tongue. The study demonstrated that on average teacher talking time in 60% comprises foreign language. Students’ first language is primarily used for teaching grammar and translating vocabulary.